Christina Gerhardt and Sara Saljoughi, editors. 1968 and Global Cinema. Wayne State UP, 2018. - Anne Cunningham (Studies in 20th & 21st Century Literature, 2019)
Review of Christina Gerhardt and Sara Saljoughi, editors. 1968 and Global Cinema. Wayne State UP, 2018. 422 pp.
Keywords: Cinema; Global; Imperialism; 1968; International Film Studies; Post Colonialism; Feminism